Modern approaches for cowpea breeding: how highthroughput genotyping and a highdensity map change everything - Ehlers, J.D.; Diop, N.N.; Ousmane, B.; Muranaka, S.; Wanamaker, S.; Issa, D.; Muchero, W.; Pottorff, M.; Cisse, N.; Roberts, P.A.; Close, T.J. (2012)
The genomics revolution has enabled rapid advances in genotyping capabilities and construction of high-density genetic linkage maps that enable new plant breeding strategies which have the potential to expedite delivery of improved crop varieties. These breeding strategies utilize molecular marker information at hundreds to thousands of points in the genome, encompassing selection for multiple traits and/or multigenic traits. This chapter summarizes the opportunities and challenges for the cowpea breeding community in adopting modern breeding given the recent development of enabling genomic resources. These resources include high-throughput SNP genotyping platforms, high-density consensus genetic map with more than 1000 markers, and QTL(s) linked to important biotic and abiotic resistance traits, including resistance to foliar and flower thrips, Fusarium wilt, root-knot nematode, bacterial blight, ashy stem blight (Macrophomina), Striga, and components of drought tolerance. Initial work in evaluating and optimizing marker-assisted backcross (MABC), marker-assisted pedigree breeding (MAPB), and marker-assisted recurrent selection (MARS) in cowpea breeding is described. We also report on the successful completion of tests evaluating the feasibility of outsourced SNP genotyping by African NARS breeders. Cost of genotyping, while much reduced compared to the recent past, is still a major constraint to widespread adoption of modern breeding by developing country NARS. High throughput precision phenotyping methods are needed to properly complement the recent advances in genomic resources. New resources and tools to help overcome these challenges have recently become available to breeders within the cowpea community, particularly in the areas of improving information management capability, decision making tools for marker-assisted breeding, and experimental design for precision phenotyping. Comprehensive training of breeders in the use of these tools is urgently needed.